Evidence-Based Medicine for Mandible Fracture Repair: Current Controversies and Future Opportunities - Barrett, Thomas; Chi, John (Facial Plastic Surgery, 2023)
Mandibular fractures are among the most common facial fractures resulting from trauma. The nature of the injury, involved facial structures, presence of associated injuries, the dental status of the patient, comorbid conditions, and psychosocial context all must be considered by the surgeon when planning the optimal treatment for these patients. While consensus exists for many aspects of the management of mandibular trauma, some elements remain controversial. Three such topics—antibiotic therapy, treatment of subcondylar fractures, and management of the third molar—remain particularly controversial, with significant heterogeneity in practice patterns and without widely accepted evidence-based guidelines to standardize care. The goals of this work are to (1) review the historical perspective underlying these controversies, (2) summarize recent evidence shaping the current debate, and (3) highlight opportunities for continued efforts to identify best practices.
Keywords: facial trauma; mandible fractures; antibiotics